The potential of five wild growing aromatic plants from Hemaq Beniung Customary Forest on antidiabetic activity - HARLINDA KUSPRADINI; AGMI SINTA PUTRI; KISWANTO KISWANTO; HAYATUS SA’ADAH; FAJRIANSYAH FAJRIANSYAH; MUHAMMAD AKMAL RIZQULLAH; ANISA GIFTA LARASATI; NAJMIA AFIFAH ZULFA; SAAT EGRA; KOSEI YAMAUCHI; TOHRU MITSUNAGA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kuspradini H, Putri AS, Kiswanto, Sa’adah H, Fajriansyah, Rizqullah MA, Larasati AG, Zulfa NA, Egra S, Yamauchi K, Mitsunaga T. 2023. The potential of five wild growing aromatic plants from Hemaq Beniung Customary Forest on antidiabetic activity. Biodiversitas 24: 2156-2162. Several aromatic plants have been used for millennia across the globe for their hyperglycemic properties. The in vitro inhibitory activity of extracts from Blumea balsamifera (L.) DC., Cinnamomum parthenoxylon (Jack) Meisn., Clausena excavata Burm.fil., Neouvaria acuminatissima (Miq.) AiryShaw, and Piper porphyrophyllum N.E.Br. were tested. The aim of this study was to determine the phytochemical constituent, total phenolic and flavonoid content of five aromatic plant extracts obtained from West Kutai, East Kalimantan as well as the antioxidant and antidiabetic activity via in vitro assays. Assays for total phenol and flavonoid content were based on Follin-Ciocalteu and aluminum chloride reagents, respectively. In this study, the antidiabetic activity was determined by measuring the inhibitory activity of ?-glucosidase enzyme, while the in vitro antioxidant activity was measured using the DPPH scavenger method. The order of inhibition of DPPH free radical was P. porphyrophyllum ethanol extract > N. acuminatissima ethanol extract > B. balsamifera ethyl acetate extract, which was found to be directly proportional to their total phenolic content. On the other hand, the order of inhibition of ?-glucosidase enzyme was found to be N. acuminatissima ethanol extract > C. parthenoxylon ethanol extract > N. acuminatissima ethyl acetate extract. Out of the 10 extracts studied, only 3 showed inhibition activity on ?-glucosidase. These findings indicate the aromatic plant extract's potential as a natural therapy for preventing and treating carbohydrate metabolic problems. As a result, the N. acuminatissima ethanol extract, which exhibits both antidiabetic and antioxidant activity, can be used in the pharmaceutical industry for the production of functional foods and herbal medicines. This is our first report on N. acuminatissima as an antioxidant and antidiabetic agent.